Peri-conception parental obesity, reproductive health, and transgenerational impacts. (February 2015) - Lane, Michelle; Zander-Fox, Deirdre L.; Robker, Rebecca L.; McPherson, Nicole O.
Highlights Maternal obesity changes oocyte composition altering lipid content and mitochondrial function. Maternal obesity-induced changes impact on embryo development, programming disease risk in offspring. Paternal obesity at conception impairs the metabolic and reproductive health of the offspring through two generations. Paternal obesity alters epigenetic marks in sperm implicating these changes in the transmission of paternal health cues to the next generation.